Pengaruh Penggunaan Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Fisika Materi Gerak Lurus Pada Siswa Kelas VII SMP Kristen Tomohon - Agustinus Elath; Heindrich Taunaumang; Patricia Mardiana Silangen (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the effect of the use of the Guided Inquiry learning model on the physics learning outcomes of straight motion material in class VIII SMP Kristen Tomohon. The samples used in this study were students of class VIII-A, Tomohon Christian Middle School. This study uses an experimental method using the same subject design (treatment by subject design). The data collection instrument used test questions which were analyzed using the t-test. The results showed that the guided inquiry learning model obtained t_count > t_table, namely 4,930 > 1,684. Thus, it can be concluded that there is an effect of using the Guided Inquiry learning model on the process and learning outcomes of students of class VIII physics in straight motion material at Tomohon Christian Middle School.